Contextual theology: skills and practices of liberating faith - Bergmann, Sigurd; Vähäkangas, Mika (Routledge, 2021)
Foreword / Robert J. Schreiter -- Doing situated theology : introductory remarks about the history, method and diversity of contextual theology / Sigurd Bergmann & Mika Vähäkangas -- Can contextual theology bridge the divide? South Africa's politics of forgiveness as an example of a contextual public theology / Dion Forster -- Contextual theology on trial : African Pentecostalism, sacred authority, and sexual and gender based violence / Chammah Kaunda -- Gender, ethnicity and lived religion : challenges to contextual and liberation theologies / Elina Vuola -- Ecumenical liberation theology : how I experienced its arrival in Germany and Europe after 1968 / Ulrich Duchrow -- Economy, greed and liberation theology : a critique from a border location in India / Atola Longkumer -- The dissemination of Vikings : postcolonial contexts and economic meltdown / Sigríður Guðmarsdóttir -- Reclaiming tradition as critique of oppression / Teresa Callewaert -- Speaking from experience : comparing Mahdawi-Pentecostal approaches to equipment for mission and its theological justification / David Emmanuel Singh -- Theology in the Anthropocene -- and beyond? / Sigurd Bergmann -- Theology of "eco-anxiety" as liberating contextual theology / Panu Pihkala -- Contextualization through the arts / Volker Küster -- World Christianity as post-colonializing of theology / Mika Vähäkangas.
Keywords: Aufsatzsammlung; Kontextuelle Theologie